Using Tactile Letters As An Assistive Technology In Teaching Alphabet For Dyslexic Children: A Case Study - Mohamed, Mariam; Tan, Abdullah (Could technology support learning efficiency?, 2017)
Dyslexia is a specific learning disability characterized by difficulties with accurate and/or fluent word recognition, poor spelling and poor decoding abilities. Dyslexic children are having language learning disorder and makes them difficult mastering the skill to read, spell and write. This research explores the design from tactile letters to mobile application that support alphabet recognition and early reading acquisition in children, particularly dyslexic children. The research design of this study is qualitative based on case study methodology. The approach of tactile letters and mobile application which could foster learning and help dyslexic children to improve some of their fundamental skills, such as recognizing alphabet and pronunciation. This study describes the design and evaluation of an assistive technology based in lieu of teaching alphabet for dyslexic children. The combination of tactile letters and mobile application may be the ground-breaking of stimulating and interactive experience for children that could encourage the learning process.
KerkoCite.ItemAlsoKnownAs: 10.12753/2066-026X-21-025 2339240:EPPXPIRH 2405685:HRGGCE4S

Parental Roles in Provision of Mobility and Educational Resources for Children with Physical Challenges a Case of Joytown Special School, Kiambu County, Kenya - Kamau, Joyce (Journal of Education and Practice, 2017)
Children with physical challenges have developmental needs and rights like other children and due to their exceptionality they call for more attention in provision of adequate quality mobility and educational resources to enhance their holistic development. However, it is apparent that provision of resources to children with physical challenges has not been possible in Kenya due to various factors which are not yet understood. The study drive was to explore parental role in the provision of mobility and educational resources to children who are physically challenged. The study sought to establish parents' involvement in provision of mobility and educational resources. The study was carried out in Joytown Primary School for the Physically Challenged in Thika Town. The school was purposefully selected because it is best suited for the study since it caters for children in the category of special needs being addressed in the study that is physical challenges. Case study design was used. Target population of the study was 100 children with physical challenges, 200 parents and 4 teachers and the head teacher. Stratified random sampling method was employed to arrive at a Sample size of 30 children with physical challenges, purposive and opportunity sampling to arrive at 30 parents and purposive sampling to arrive at 4 teachers. Therefore, the total sample size was 64. The data were collected using various techniques which included questionnaires for the teachers, interview guides for parents and observation guides for children. Collected data were analyzed using both quantitative and qualitative methods. Quantitative methods entailed use of descriptive statistics such as frequencies and percentages which enhanced discussion of qualitative data which was organized into themes and categories and presented in discussion form. The study established that parental involvement in provision of mobility and educational resources is minimal. The main recommendation of the study is that government should have a budgetary allocation meant specifically for purchase of mobility and educational resources and maintenance of facilities since it's a noble course which would ensure that children are actively involved in learning activities therefore enhancing holistic development hence molding children with physical challenges to become self-reliant and productive citizens.
Publisher: IISTE KerkoCite.ItemAlsoKnownAs: 2339240:VXMFTYG8 2405685:8FZZT8ZT
Keywords: Assistive Technology; Case Studies; Child Development; Educational Resources; Elementary School Students; Elementary School Teachers; Foreign Countries; Interviews; Observation; Parent Participation; Parent Role; Physical Disabilities; Physical Mobility; Questionnaires; Resource Allocation; Special Schools; Statistical Analysis; ⛔ No DOI found

Female Teachers' Perceptions of Quality Education for Adolescent Girls in Rural Bangladesh: A Case Study - Rahim, N (2017)
The education of adolescent girls in Bangladesh must be pursued with the right combination of technology, practicality, and cultural sensitivity to achieve, among other objectives, the objectives of Millennium Development Goals (MDGs). The problem this study address is despite the availability of mobile-based curricula, such as video, mobile phones, and Short Message System (SMS) technology, female teachers in rural areas are not trained to plan and deliver curricula using mobile platforms. The purpose of this qualitative single case study is to explore barriers associated with female teachers’ training of the use of mobile-based technology in rural areas in Bangladesh. The sample is, randomly selected a minimum of eight local female teachers who had been teaching at least for two years in a rural school in Bangladesh. The data were collected to determine the local teachers’ perception on establishing quality education through virtual (email, mobile phone, IMO, zoom or Skype) interviews administered to these 8 local female teachers. The researcher gathered data from the local female teachers’ point of view based on their motivation to receive training in becoming proficient in English and the use of mobile technology in teaching. A content analysis tool was used for analyzing, interpreting, coding, and categorizing textual data where themes identified based on a comprehensive classification system. The findings from the data analysis would aid schools in recruiting, training, and retaining local female teachers to provide quality education to the adolescent girls. The data from the single case study provided information as to the use of mobile and web technologies in teaching and learning while local female teachers gain proficiency in the English language. The insight gained from this single case study may help develop future technology budgets, infrastructure, and curriculum needs. The findings from research revealed that the rural Bangladeshi school teachers noted that there is limited use of videos in the classrooms for teaching due to, in some parts, the lack of training by school administrators on strategies to use videos in their teaching. Some barriers to the use of videos is due to the lack of Internet connection, the lack of knowledge on the proper use of videos in their teaching, and the lack of administrators’ support for this type of curriculum change in the schools.
KerkoCite.ItemAlsoKnownAs: 2339240:MKU6GYRJ 2405685:VDGJUDEZ

Performance Oriented Information and Communication Technology (ICT): Model for Education Purpose in Pakistan. A Bahawalpur District Case Study - Qadri, Salman; Shah, Rehan Ali; ul Rehman, Muzammil; Ullah, Saleem; Shah, Ali Nawaz; Ali, Muhammad Zaman; Ahmed, Muhammad Munawer (International Journal of Computer Science and Network Security, 2017)
Information technology brought a dramatic change in our society. In third world countries such as Pakistan is also trying to get involve this technology in every field of life. In this decade, information technology is being used in several disciplines such as education, health, agriculture and business etc. It has given a positive impact on all of these disciplines especially E-banking, E-learning and E-commerce etc. This study focuses the implementation of information and communication technology (ICT) framework to boost the progress of different less develops areas in Pakistan. This study also describes the complete methodology with all of its benefits and constraints on implementation and also proposed a framework to improve the efficiency and accuracy in education department in primary to higher level in Bahawalpur district and its five sub districts (tehsil) and also take the case study of The Islamia University Bahawalpur within city sub campuses by utilizing the successful implementation of information and communication technology for the betterment of education.
Place: Seoul Publisher: Int Journal Computer Science & Network Security-Ijcsns WOS:000411617300049 KerkoCite.ItemAlsoKnownAs: 2339240:73XAL6FN 2405685:XNN6758Y
Keywords: E-Classes; ICT Infrastructure; IT-Centers; Information and Communication Technology; integration; teachers; ⛔ No DOI found

Interrogating Gender Divides in Technology for Education and Development: the Case of the One Laptop per Child Project in Ghana - Steeves, Leslie; Kwami, Janet (Studies in Comparative International Development, 2017)
The One Laptop per Child (OLPC) project aims to make low-cost computers accessible to the “world’s poorest children,” presuming that the gadgets will support their empowerment via education. The project’s success globally, however, has been mixed at best, with many countries terminating their purchases due to cost, inadequate infrastructure, and negative side effects. In October 2010, Ghana suspended the country’s 3-year participation. This study examines the complex history and failure of OLPC Ghana in two pilot schools, one urban and one rural, with particular attention to gender bias. The analysis draws on interviews with government personnel, students, and teachers in the pilot classes. Despite lacking electric power in the rural community, UNDP’s Millennium Villages Project played a strong support role, making OLPC somewhat more effective with less of a gender divide in the rural school than in the urban school in Accra. Both pilot schools faced severe sustainability challenges raising decade-old questions about modernity and technological determinism. Further, in both schools, particularly the urban school, a digital divide by gender was evident.
shortDOI: 10/ggtsmj KerkoCite.ItemAlsoKnownAs: 10.1007/s12116-017-9245-y 10/ggtsmj 2339240:DKVPCJ4N 2405685:EBIDU596 2405685:EHX857GT
Keywords: C: Ghana

Education technology: An evidence-based review - Escueta, Maya; Quan, Vincent; Nickow, Andre Joshua; Oreopoulos, Philip (National Bureau of Economic Research, 2017)
In recent years, there has been widespread excitement around the potential for technology to transform learning. As investments in education technology continue to grow, students, parents, and teachers face a seemingly endless array of education technologies from which to choose—from digital personalized learning platforms to educational games to online courses. Amidst the excitement, it is important to step back and understand how technology can help—or in some cases hinder—how students learn. This review paper synthesizes and discusses experimental evidence on the effectiveness of technology-based approaches in education and outlines areas for future inquiry. In particular, we examine RCTs across the following categories of education technology: (1) access to technology, (2) computer-assisted learning, (3) technology-enabled behavioral interventions in education, and (4) online learning. While this review focuses on literature from developed countries, it also draws upon extensive research from developing countries. We hope this literature review will advance the knowledge base of how technology can be used to support education, outline key areas for new experimental research, and help drive improvements to the policies, programs, and structures that contribute to successful teaching and learning.
KerkoCite.ItemAlsoKnownAs: 10.3386/w23744 2339240:3BIGHYQN 2339240:FYC7BPHW 2339240:LYBI56IU 2405685:63EDEAFD 2405685:AEIV8XGY 2405685:AWIHDCCP
Keywords: ___working_potential_duplicate

MOOCs for in-service teachers: the case of Uganda and lessons for Africa - Oyo, B.; Kalema, B.M.; Byabazaire, J. (Revista Española de Pedagogía, 2017)
In recent times, computers and internet have penetrated secondary schools in Africa but with greater attention to students’ computer literacy than teachers. At the same time, previous studies on digital literacy of teachers are unsustainable and mainly skewed on pre-service teachers than in-service teachers. These realities point to the need to investigate and implement effective and sustainable initiatives for improving digital literacy and online life-long learning for in-service teachers in Africa. This paper therefore presents a specialised MOOC platform known as TEP (Teachers’ E-learning Portal) for digital literacy and online life-long learning for in-service teachers in Uganda. TEP is built for environments with inadequate access to computers, internet and technical assistance. As such, TEP is accessible online or offline, managed by accredited local universities in collaboration with beneficiary secondary schools, and runs on existing resources in schools (technical personnel, computers and internet). Results from initial implementation of a computer literacy MOOC through TEP indicate that irrespective of age, when teachers are adequately supported internally by their schools and externally by a university, can improve their digital literacy and subsequently engage in online life-long learning. In addition, the results both in terms of high percentage of teacher participants’ completions (89%) and high volume of educational e-content generated, confirm TEP as an effective, attractive, and self-sustainable MOOC platform for in-service teachers’ in resource constraint environments. The paper finishes with an analysis of the relevance of TEP to Africa.
Extra URL: https://revistadepedagogia.org/en/lxxv-en/no-266/moocs-for-in-service-teachers-the-case-of-uganda-and-lessons-for-africa/101400005980/ KerkoCite.ItemAlsoKnownAs: 10.22550/rep75-1-2017-07 10/ggddgs 2339240:MR2W67VK 2405685:USHUUTDI 2534378:VFQKYSXZ 2534378:WLCXEHHM
Keywords: _Source:Intuitive; _THEME: Education management; _THEME: Teacher Professional Development; __:import:03; __:match:final; __:matched; __:study_id:2426079; __finaldtb

MOOCs for in-service teachers: the case of Uganda and lessons for Africa - Oyo, B.; Kalema, B.M.; Byabazaire, J. (Revista Española de Pedagogía, 2017)
In recent times, computers and internet have penetrated secondary schools in Africa but with greater attention to students’ computer literacy than teachers. At the same time, previous studies on digital literacy of teachers are unsustainable and mainly skewed on pre-service teachers than in-service teachers. These realities point to the need to investigate and implement effective and sustainable initiatives for improving digital literacy and online life-long learning for in-service teachers in Africa. This paper therefore presents a specialised MOOC platform known as TEP (Teachers’ E-learning Portal) for digital literacy and online life-long learning for in-service teachers in Uganda. TEP is built for environments with inadequate access to computers, internet and technical assistance. As such, TEP is accessible online or offline, managed by accredited local universities in collaboration with beneficiary secondary schools, and runs on existing resources in schools (technical personnel, computers and internet). Results from initial implementation of a computer literacy MOOC through TEP indicate that irrespective of age, when teachers are adequately supported internally by their schools and externally by a university, can improve their digital literacy and subsequently engage in online life-long learning. In addition, the results both in terms of high percentage of teacher participants’ completions (89%) and high volume of educational e-content generated, confirm TEP as an effective, attractive, and self-sustainable MOOC platform for in-service teachers’ in resource constraint environments. The paper finishes with an analysis of the relevance of TEP to Africa.
Extra URL: https://revistadepedagogia.org/en/lxxv-en/no-266/moocs-for-in-service-teachers-the-case-of-uganda-and-lessons-for-africa/101400005980/ KerkoCite.ItemAlsoKnownAs: 10.22550/rep75-1-2017-07 10/ggddgs 2339240:HPI63QSH 2339240:MR2W67VK 2405685:CIF2AFNW 2534378:WLCXEHHM
Keywords: _Source:Intuitive; _THEME: Education management; _THEME: Teacher Professional Development; __:import:03; __:match:final; __:matched; __:study_id:2426079; __finaldtb

Interrogating gender divides in technology for education and development: The case of the one laptop per child project in Ghana - Steeves, H. Leslie; Kwami, Janet (Studies in Comparative International Development, 2017)
The One Laptop per Child (OLPC) project aims to make low-cost computers accessible to the “world’s poorest children,” presuming that the gadgets will support their empowerment via education. The project’s success globally, however, has been mixed at best, with many countries terminating their purchases due to cost, inadequate infrastructure, and negative side effects. In October 2010, Ghana suspended the country’s 3-year participation. This study examines the complex history and failure of OLPC Ghana in two pilot schools, one urban and one rural, with particular attention to gender bias. The analysis draws on interviews with government personnel, students, and teachers in the pilot classes. Despite lacking electric power in the rural community, UNDP’s Millennium Villages Project played a strong support role, making OLPC somewhat more effective with less of a gender divide in the rural school than in the urban school in Accra. Both pilot schools faced severe sustainability challenges raising decade-old questions about modernity and technological determinism. Further, in both schools, particularly the urban school, a digital divide by gender was evident.
15 citations (Crossref) [2024-04-29] KerkoCite.ItemAlsoKnownAs: 10.1007/s12116-017-9245-y 2339240:4VMARDY3 2405685:S4AUFT59
Keywords: Development; Gender; Ghana; Information communication technology (ICT); Internet; ⛔ No INSPIRE recid found

Tusome Midline evaluation 2017 final report from DEC - Freudenberger, Elizabeth; Davis, Jeff (2017)
KerkoCite.ItemAlsoKnownAs: 2339240:3KWQGK3D 2405685:IWDPTBQN
Keywords: ⚠️ Invalid DOI

Empowered educators: how high-performing systems shape teaching quality around the world - Darling-Hammond, Linda (Jossey-Bass, 2017)
KerkoCite.ItemAlsoKnownAs: 2339240:NPLPX7IV 2405685:VS6WIN6M
Keywords: Case studies; Education and state; Teachers; Training of

Blog-based professional development of English teachers in Mumbai: the potential of innovative practice under scrutiny - Khan, Atiya (Australasian Journal of Educational Technology, 2017)
The professional development of teachers in India is still, by and large, based on formal and outdated professional learning traditions, often characterised by crash courses and one-off workshops. In education, blogs have proven to be an effective means of establishing and maintaining collaborative learning networks and helping members reflect on their professional practices. Information and communications technology (ICT) enabled practices of teacher professional development is still in its infancy in India. Moreover, there is limited research in India to secure foundational understanding of how and in what ways teachers of English in India use blogs for their professional development. This study explores the use of teacher reflective practice, teacher networking, and teacher collaboration, beyond formal ICT training, through blog-based professional development of English teachers in the Mumbai region of India. Using data collected from 32 teachers from three private schools in Mumbai, through ICT interactive workshop observations, questionnaires, interviews, and blog comments, this action case study explains whether and why blogging, as a learning community, has the potential to add significant value to existing professional development of English teachers in Mumbai.
Publisher: Australasian Society for Computers in Learning in Tertiary Education, Ascilite Secretariat, P.O. Box 44, Figtree, NSW, Australia Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/1969007459?accountid=9851 KerkoCite.ItemAlsoKnownAs: 10.14742/ajet.2784 2405685:EPKS7TDM 2534378:MQYLKXN6 2534378:Y6KUBK5K
Keywords: Action Research; Case Studies; Communities of Practice; Diaries; ERIC; Current Index to Journals in Education (CIJE); Electronic Publishing; English (Second Language); Faculty Development; Foreign Countries; India; Language Teachers; Participant Observation; Private Schools; Qualitative Research; Questionnaires; Reflective Teaching; Second Language Instruction; Semi Structured Interviews; Teacher Collaboration; Web Sites; Workshops; __:import:01; __:match:final; __:matched; __:study_id:2096053; __finaldtb

Case Study Report: RET International Kenya - Boisvert, Kayla (University of Massachusetts Amherst, 2017)
KerkoCite.ItemAlsoKnownAs: 2339240:ZPJGD9MB 2405685:SACV4G7Q

Investigations into using data to improve learning: Philippines case study - Read, Lindsay; Atinc, Tamar Manuelyan (Global Economy and Development at Brookings, 2017)
KerkoCite.ItemAlsoKnownAs: 2339240:CY4FPYE7 2405685:MDKQZGJ4

Open Government Case Study: Costing Sierra Leone’s Open Data Program - Joswiak, Naomi (Results for Development, 2017)
KerkoCite.ItemAlsoKnownAs: 2405685:AN5GA9QR
Keywords: ___working_potential_duplicate

Open Government Case Study: Costing Sierra Leone’s Open Data Program - Joswiak, Naomi (Results for Development, 2017)
KerkoCite.ItemAlsoKnownAs: 2339240:ZNYWJ9PF 2405685:7HSIXMSV
Keywords: ___working_potential_duplicate

Using tactile letters as an assistive technology in teaching alphabet for dyslexic children: A case study - Mohamad, M.; Abdullah, S. J. T. (eLearning and Software for Education, 2017)
KerkoCite.ItemAlsoKnownAs: 10.12753/2066-026x-17-025 2339240:NJ9RXN6L 2405685:QAAA3NFG

Using Tactile Letters As An Assitive Techology in Teaching Alphabet For Dyslexi Children: A Case Study - Mohamad, Mariam; Tan, Abdullah; Sabrina, Jessica (eLearning & Software for Education, 2017)
KerkoCite.ItemAlsoKnownAs: 2339240:BSQCEEJM 2405685:9W7TB9SK
Keywords: ⛔ No DOI found

Teachers’ conception towards the use of social networks as a tool for professional development in Tanzania government secondary schools: the case of Dodoma municipality - Manyama, Charles (University of Dodoma, 2017)
The current study sought to assess teachers' conception toward the use of social networks as a tool for professional development in Tanzania government secondary schools the case of Dodoma Municipality. Thus, the specific objectives of this study were to assess the influence of demographic characteristics on the use of social networks or as a tool for professional development. To assess teachers conception on the available social networks opportunity that can support professional development, to investigate teachers use of social networks available for professional development, to explore the perceived benefits of using social networks opportunity as a tool for professional development and to examine limitation that hinder teachers for professional development. The study was guided by social-cognitive theory, community of practice model (CoP) and technology acceptance model (TAM). A cross-section research design was used to collect data that involved 84 teachers‟ from ten secondary schools, six head of schools three quality assurers and one respondent from DEO office. SPSS computer program was used to analyze the data. Qualitative data were analyzes through content analysis and quantitative data were analyzed statistically using descriptive and inferential statistics by using SPSS Version 20, and Microsoft Excel were highly used. Linear regression techniques were used to seek whether there is a relationship between demographic characteristics and the use of social networks. The survey results showed that there is no significant relationship between demographic factors with the use of social networks as a tool for professional development. Either teachers have positive conceptions towards the use of social networks as a tool for professional development. Furthermore, teachers use SNs for communicating with their fellow from different groups but it is not effectively integrated into professional development. The findings indicate that, to a large extent, teachers agreed that SNs make them to be more creative and help them to improve their communication skills. In addition the findings indicated that teachers lack training on how to integrate SNs in TPD. Finally,the researcher recommend that, educational stakeholders should provide financial and material support to teachers in order to overcome challenge that limit the use of technology in teaching and learning.
Accepted: 2018-04-11T09:35:23Z Publisher: The University of Dodoma KerkoCite.ItemAlsoKnownAs: 2339240:YDEVGFS3 2405685:U59ER7CF
Keywords: ⛔ No DOI found

Not just for special occasions: supporting the professional learning of teachers through critical reflection with audio-visual information - Saito, Eisuke; Khong, Thi Diem Hang (Reflective Practice, 2017)
Despite increased use of professional learning communities in the teacher education field, they do not necessarily guarantee change in teachers’ daily practice. This study is a multiple case study of three school leaders in Vietnam to connect their teachers’ learning and practice by utilising visual records. In the cases studied, we see a progression of models of joint reflection based on visual information, from only occasional reflection to daily critical reflection, the latter of which the authors call ‘vide-flection’ referring to a process for people to consider their actions, thoughts, or experiences by utilising video-recorded images. For joint vide-flection, school leaders visit every classroom for several minutes every day to observe the wellbeing and learning of pupils and video-record struggles or breakthroughs in children’s learning; they share those images with teachers to jointly reflect on the situations. Through this vide-flection, teachers develop more detailed awareness of pupils needs. [ABSTRACT FROM PUBLISHER]
Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.ebscohost.com/login.aspx?direct=true&db=bri&AN=126003617&site=ehost-live&scope=site KerkoCite.ItemAlsoKnownAs: 10.1080/14623943.2017.1361921 2405685:BC5IPJP7 2534378:8GYBJJ8Z 2534378:R2HCJDDM
Keywords: ADULTS; AUDIOVISUAL aids in education; AUDIOVISUAL materials; CRITICAL thinking studies; DATA analysis software; DESCRIPTIVE statistics; EDUCATION; FOCUS groups; INTERVIEWING; PROFESSIONAL education; PROFESSIONAL employee training; REFLECTION (Philosophy); RESEARCH funding; Reflective practice; SCHOOL administrators; TEACHER training; TEACHING; THEMATIC analysis; VIETNAM; Vietnam; __:import:01; __:match:final; __:matched; __:study_id:2099873; __finaldtb; critical reflection; professional learning; teacher professional development; vide-flection

Integrating ICT into Teaching and Learning Biology: A Case for Rachuonyo South Sub-County, Kenya - Mwanda, Gideon; Mwanda, Samwel; Midigo, Ronnie; Maundu, John (American Journal of Education and Information Technologies, 2017)
The purpose of this study was to find out the extent of integration of computer technology into teaching and learning Biology in secondary schools of Rachuonyo South Sub-County, Kenya. The target population consisted of students and biology teachers in the Sub-County. Data was collected by use of questionnaires and an observation check list. From the study, most schools had few computers; teachers had inadequate training on use of computer applications; most teachers did not use computer technology for personal growth and instructional purposes. Inadequate number of computers in the sampled schools was the major challenge facing the integration of computer technology into the instruction process. The study recommends increased accessibility of computers, adequate training on use of computer technology and development of a policy framework to guide on the path to effective computer integration into instruction process.
KerkoCite.ItemAlsoKnownAs: 10.11648/j.ajeit.20170102.12 2339240:BB268PHG 2405685:N3QTNN5K
Keywords: ⚠️ Invalid DOI

Not just for special occasions: supporting the professional learning of teachers through critical reflection with audio-visual information - Saito, Eisuke; Khong, Thi Diem Hang (Reflective Practice, 2017)
Despite increased use of professional learning communities in the teacher education field, they do not necessarily guarantee change in teachers’ daily practice. This study is a multiple case study of three school leaders in Vietnam to connect their teachers’ learning and practice by utilising visual records. In the cases studied, we see a progression of models of joint reflection based on visual information, from only occasional reflection to daily critical reflection, the latter of which the authors call ‘vide-flection’ referring to a process for people to consider their actions, thoughts, or experiences by utilising video-recorded images. For joint vide-flection, school leaders visit every classroom for several minutes every day to observe the wellbeing and learning of pupils and video-record struggles or breakthroughs in children’s learning; they share those images with teachers to jointly reflect on the situations. Through this vide-flection, teachers develop more detailed awareness of pupils needs.
Publisher: Routledge _eprint: https://doi.org/10.1080/14623943.2017.1361921 KerkoCite.ItemAlsoKnownAs: 10.1080/14623943.2017.1361921 2339240:UPNEHQVJ 2405685:8CQU3AHD
Keywords: Reflective practice; Vietnam; critical reflection; professional learning; teacher professional development; vide-flection

Blog-based professional development of English teachers in Mumbai: The potential of innovative practice under scrutiny | Australasian Journal of Educational Technology - Khan, Atiya (Australian Journal of Educational Technology, 2017)
The professional development of teachers in India is still, by and large, based on formal and outdated professional learning traditions, often characterised by crash courses and one-off workshops. In education, blogs have proven to be an effective means of establishing and maintaining collaborative learning networks and helping members reflect on their professional practices. Information and communications technology (ICT) enabled practices of teacher professional development is still in its infancy in India. Moreover, there is limited research in India to secure foundational understanding of how and in what ways teachers of English in India use blogs for their professional development. This study explores the use of teacher reflective practice, teacher networking, and teacher collaboration, beyond formal ICT training, through blog-based professional development of English teachers in the Mumbai region of India. Using data collected from 32 teachers from three private schools in Mumbai, through ICT interactive workshop observations, questionnaires, interviews, and blog comments, this action case study explains whether and why blogging, as a learning community, has the potential to add significant value to existing professional development of English teachers in Mumbai.
KerkoCite.ItemAlsoKnownAs: 10.14742/ajet.2784 2339240:MKUUJUI9 2405685:XDE87UXV

Thematic Analysis: Striving to Meet the Trustworthiness Criteria - Nowell, Lorelli S.; Norris, Jill M.; White, Deborah E.; Moules, Nancy J. (International Journal of Qualitative Methods, 2017)
As qualitative research becomes increasingly recognized and valued, it is imperative that it is conducted in a rigorous and methodical manner to yield meaningful and useful results. To be accepted as trustworthy, qualitative researchers must demonstrate that data analysis has been conducted in a precise, consistent, and exhaustive manner through recording, systematizing, and disclosing the methods of analysis with enough detail to enable the reader to determine whether the process is credible. Although there are numerous examples of how to conduct qualitative research, few sophisticated tools are available to researchers for conducting a rigorous and relevant thematic analysis. The purpose of this article is to guide researchers using thematic analysis as a research method. We offer personal insights and practical examples, while exploring issues of rigor and trustworthiness. The process of conducting a thematic analysis is illustrated through the presentation of an auditable decision trail, guiding interpreting and representing textual data. We detail our step-by-step approach to exploring the effectiveness of strategic clinical networks in Alberta, Canada, in our mixed methods case study. This article contributes a purposeful approach to thematic analysis in order to systematize and increase the traceability and verification of the analysis.
shortDOI: 10/gfzk5k KerkoCite.ItemAlsoKnownAs: 10.1177/1609406917733847 10/gfzk5k 2339240:MA82VRXM 2405685:N7WTRMQI

“Thinking Outside the Camp”: Education Solutions for Syrian Refugees in Jordan - Baeyer, Sarah Lebaron Von (Ethnographic Praxis in Industry Conference Proceedings, 2017)
This paper presents a case study of a project on education solutions for Syrian refugees in Jordan conducted between 2015–2017. First, it describes how ReD's methodological approach provided a unique perspective to studies on refugees. By immersing a team in the day-to-day lives and settings that most Syrian refugees experience in Jordan—i.e., outside of camps and in people's actual homes—ReD led its client to “think outside the camp,” something that relief agencies and companies often fail to do due to the refugee camp model of humanitarian assistance that, ever since WWII, has dominated the approach to refugees. Second, as a result of its unique methodological approach, ReD uncovered important findings about social networks and technology use and access in Syrian refugees’ homes and communities that ultimately shaped the client's perspective on solution development. For example, ReD's team of ethnographers found that nearly all out-of-camp Syrian households had at least one Smartphone in their possession, if not two or more, and that digital devices served as important tools of communication and community-building among people displaced by conflict. Consequently, ReD advised its client to tap into these pre-existing social networks and mobile technologies in order to develop an education solution that best fit refugees’ “real-life” practices. Ultimately, both ReD's methods and its findings led to a significant impact in how the client strategized on and developed their education solution, and can serve as a broader model for how to approach building services and/or products for displaced populations with access to basic mobile technologies. “The Jordanian educational/policy response to refugees is broken and will not easily be fixed or tinkered with. Solutions must work around this system.” (Education expert and activist working with vulnerable youth and school dropouts in Jordan)
_eprint: https://anthrosource.onlinelibrary.wiley.com/doi/pdf/10.1111/1559-8918.2017.01163 shortDOI: 10/ggtdgp KerkoCite.ItemAlsoKnownAs: 10.1111/1559-8918.2017.01163 10/ggtdgp 2339240:PSJ2UYDF 2405685:PHYHJPGI
Keywords: Google Scholar/ refugee education technology; RER theme_durable solutions

Higher education reforms: Latin America in comparative perspective - Bernasconi, Andrés; Celis, Sergio (Education Policy Analysis Archives, 2017)
This article introduces a special issue of EPAA/AAPE devoted to recent higher education reforms in Latin America. The last two decades have seen much policy development in higher education in the region, examined and discussed by scholars in each country, but dialog with the international literature on higher education reform, or an explicit comparative focus, have been mostly absent from these works. By way of presentation of the papers included in this issue, we first provide an overview of major policy changes in higher education in the Latin American region since the 1990s. We then turn to the six works in this special issue to describe the theories and methods supporting them. Next, we illustrate how general analytic categories can be derived from single or multi country case studies to illuminate themes capable of cutting across the particulars of national contexts, with their unique traditions, policy paths, and politics. Our three common threads are, first, the types of drivers for reform, that is, how policy change originates, either bottom-up from the institutions, or top-down from the government, and various possibilities in between. Second, understanding challenges to institutional autonomy in a continuum of intensity of state intended intervention in higher education. Third, explaining different levels of strain between public and private sectors in higher education based on conditions of competition for economic resources. While the papers in this special issue do not cover all countries, nor all issues on which policy has been crafted in the last two decades across the region, the collection of articles herein account for topics of enduring importance: faculty work in Ecuador, financial aid in Colombia, public policy decentralization in Argentina, quality assurance models in Colombia and Uruguay, the emerge of new institutions and universities in Argentina and Uruguay, and social justice, access, and inclusion in higher education, in Argentina, Bolivia, Brazil, Chile, Colombia, and Ecuador. The articles presented in this special issue provide much insight onto higher education policy in Latin America and, additionally, offer ample opportunity to develop social science knowledge on the basis of strong comparative work.
KerkoCite.ItemAlsoKnownAs: 10.14507/epaa.25.3240 2339240:4M24F399 2405685:RNRQL9Z2
Keywords: Change in universities